PI3Kγ is a novel regulator of TNFα signaling in the human colon cell line HT29/B6. Issue 1 (20th June 2022) - Klaus, Franz‐Leonard; Kirsch, Cornelia; Müller, Jörg P.; Huber, Otmar; Reiche, Juliane
Abstract: Phosphoinositide 3‐kinases (PI3Ks) are a family of enzymes phosphorylating phospholipids in the membrane, thereby, promoting the PI3K/AKT signaling cascade. PI3Ks are involved in a variety of fundamental cellular functions, including tumor necrosis factor α (TNFα)‐induced tight junction (TJ) impairment—a hallmark of inflammatory bowel diseases. Most of the studies analyzing the role of class I PI3K signaling in epithelial barrier maintenance did not decipher which of the isoforms are responsible for the observed effects. By using wild‐type and PI3Kγ‐deficient HT‐29/B6 cells, we characterized the functional role of PI3Kγ in these cells under inflammatory conditions. Measurement of the transepithelial electrical resistance and the paracellular flux of macromolecules revealed that monolayers of PI3Kγ‐deficient cells, compared with wild‐type cells, were protected against TNFα‐induced barrier dysfunction. This effect was independent of any PI3K activity because treatment with a pan‐PI3K inhibitor did not alter this observation. By immunostaining, we found correlative changes in the distribution of the TJ marker ZO‐1. Furthermore, the absence of PI3Kγ reduced the basal level of the pore‐forming TJ protein claudin‐2. Our study suggests a novel noncanonical, kinase‐independent scaffolding function of PI3Kγ in TNFα‐induced barrier dysfunction. Abstract : We evaluated the role of class I PI3Kγ in the setting of TNFα‐mediated barrier breakdown in human HT‐29/B6 colon carcinoma cells by comparing wild‐type and PI3Kγ catalytic subunit–deficient cells. We provide evidence that loss of PI3Kγ in HT‐29/B6 cells affects basal regulation of claudin‐2, and that the scaffolding function of PI3Kγ mediates the barrier breakdown induced by TNFα.